FAKTOR RISIKO KANKER PAYUDARA PADA WANITA DI RSUD PANEMBAHAN SENOPATI BANTUL - Dwi Kartika Rukmi; Dwi Handayani (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: The incidence of breast cancer is increasing, particularly in previously low incidence areas such as Asia. In fact in Indonesia, it is considered as the leading cancer among women in certain metro such as Yogyakarta. The exact etiology of breast cancer remains unknown but the risk factors responsible for the causation of breast cancer may be population specific. Identifying these factors holds great promise in reducing the incidence, morbidity and mortality due this disease. Objective: To unveil risk factors related to breast cancer cases in Panembahan Senopati Hospital of Bantul. Methods: This study applied case control study method with 33 respondents for either case group or control group involved inclusion criteria. Data were surveyed by using a purposeful questionnaire and data of breast cancer cases was attained from patient’s medical record. Data analysis applied Chi-Square (α=0.05) and double logistic regression. Results: Risk factors related to breast cancer cases according to multivariable analysis were; age of first pregnancy >30 years old (OR: 44,67;CI: 3,25–614,11; p=0,004), Parity History >2 children (OR: 10,07;Cl:1,59–63,91; p=0,014), age of menarche <12 (OR : 15,84; CI: 1,27–198,29;p=0,032), age of menopause >55 years old (OR: 0,007;CI: 0,00–0,18; p=0,003), and history of benign tumor infection (OR:62,15;CI: 3,33–1158,97; p=0,006). History of benign tumor infection was the risk factor with the most significant influence. The result of dual variable test with chi-square described a relation between age >30 years old, history of exclusive breastfeeding, radiation exposure, family history, and application of hormonal contraceptive. Conclusions: Risk factors that had relations to breast cancer cases were age of first pregnancy >30 years old, parity history >2 children, age of menarche <12 years old, age of menopause >55 years old, and history of benign tumor infection. Keywords: Breast cancer, risk factors